A Child with a Painful Foot: How to Get a Definitive Diagnosis. (8th March 2022) - van de Kimmenade, R. J. L. L.; Meijer, D. T.; Hoornenborg, D.; van der Vis, H. M.
Abstract : This case report describes an 8-year-old healthy boy with a retained wooden foreign body in his 4 th metatarsal bone of his right foot. He was presented several months after the initial trauma, stepping into a toothpick, had occurred. He was operated in our hospital, and the wooden toothpick was removed. The operation and recovery were both uncomplicated. History and physical examination are essential in these types of cases with a history of penetrating trauma but can be inconclusive due to the delay in presentation. Aggressive treatment on the other hand is necessary to prevent bigger problems such as the development of inflammatory problems and persisting complaints. A thorough, systematic, and complete work-up from the history to treatment is therefore necessary and will be described in this case report.